Penerapan Corporate Social Responsibility (CSR) di Semen Gresik (Persero) Tbk. - Arief Maffuron, (Pendidikan Ekonomi, 2011)
PT. Semen Gresik (Persero) Tbk implements CSR commonly known as Partnership ad Community Development which is based on triple bottom line. The triple bottom line refers to society, economy, and environment. The economic program is related to small scale business partnership in terms of soft loan and grant. In terms of society and environemt, the programs include aids for natural disaster, education, infrastructure, worship places, natural preservation. The budget already disburst by PT Semen Gresik for small scale partnership amounted to 1.5 % anf for community development was up to 1 %.